The Relationship Between Learning Motivation and Academic Procrastination in Final Year Students in the Covid-19 Endemic Era - Ramm Natarezwa*, Mohammad Kahmed; Heng, Pamela Hendra (Universitas Syiah Kuala, 2023)
Currently, we have entered the endemic phase of COVID - 19 which has changed the learning system a lot. Final - year students in the COVID-19 endemic phase are required to adapt to the changes that are occurring. Examples of changes that can occur are learning motivation and academic procrastination. Motivation to learn is the presence of strength and driving force within which functions as a builder of desire and willingness to take action so as to achieve goals. Academic procrastination has the meaning of suspending or delaying the completion of a task and is categorized as a failure of self-regulation. This study aims to determine the relationship between learning motivation and academic procrastination in final-year students of the COVID-19 endemic era. This research was carried out using a correlational quantitative method. Researchers used a purposive sampling method to find participants. The participants of this study were 165 final semester students aged 21-25 years at X University in Jakarta, who have domicile origins from Java Island, Kalimantan Island, Sulawesi Island and Sumatra Island. Motivation was measured using the Academic Motivational Scale - Short Indonesian Language Version (AMS-SILV) ( = .832) and academic procrastination was measured using the Academic Procrastination Scale (APS) ( = .91). Due to the abnormal distribution of the data, the data was processed using the Spearman correlation test which obtained a sig. = 1.000 and the value of r = 0.091 which means that learning motivation has no significant relationship with academic procrastination.